Psychiatric Disorders and ADD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The frequencies of various psychiatric and neuromaturational disorders were compared in 22 ADD children aged 5-16 yrs and in 20 normal control subjects studied by structured diagnostic interviews with mothers in the Pediatric Psychopharmacology Clinic and Child Psychiatry Service, Massachusetts General Hospital, Boston.